Analysis of the Meaning of Repetition Language Style in Hermann Hesse's Der Steppenwolf Roman - Purwanto, Anim; Zuriyati, Zuriyati; Anwar, Miftahulkhairah (Journal International of Lingua and Technology, 2024)
Repetitive language style in romance literary works is not only used to create aesthetic effects, but also creates emotional and intellectual resonance that enriches the reading experience. This study aims to analyze the meaning of repetition language style in the romance Der Steppenwolf by Hermann Hesse. The research uses descriptive qualitative method with semantic analysis approach. The analysis revealed that anaphora is the most dominant language style used, with the amount of data reaching 40.74%, followed by epistrophe around 31.48%, and polysyndeton 27.78% of data. Meanwhile, the meaning of repetition language style includes strengthening the character's feelings towards the world, providing structure and rhythm to the story, creating nuances and deep emotions. Repetitive language styles in romances can provide new insights into how literary works are constructed and influence readers.